2021
DOI: 10.7717/peerj.12174
|View full text |Cite
|
Sign up to set email alerts
|

The expansion and diversity of theCYP75gene family in Vitaceae

Abstract: The CYP75 gene family plays an important role in flavonoid biosynthesis in plants. Little is known about the evolution of the gene family within the grape family. Here, we extracted the CYP75 genes from transcriptome data of 15 grape species and 36 representative genomes from other plants to explore the evolutionary history of the CYP75 gene family in Vitaceae. The structure of the CYP75 protein sequences is highly conserved with the variation mainly occurring in the N terminal and the middle region. The evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…Phylogenetic analysis of existing sequences of CYP75 s revealed that CYP75A was derived from CYP75B prior to the divergence of angiosperms and gymnosperms ( Seitz et al., 2006 ). It is demonstrated that the CYP75B subfamily has perhaps a more superior evolutionary position in the CYP75 gene family, performing not only in its own function, but sometimes work as compensation for the CYP75A subfamily ( Xiao et al., 2021 ). In this study, all orchid CYP75 s were found to be located on the endoplasmic reticulum, as previous research has shown that CYP450 is a membrane protein primarily found on the ER membrane in eukaryotes ( Brignac-Huber et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of existing sequences of CYP75 s revealed that CYP75A was derived from CYP75B prior to the divergence of angiosperms and gymnosperms ( Seitz et al., 2006 ). It is demonstrated that the CYP75B subfamily has perhaps a more superior evolutionary position in the CYP75 gene family, performing not only in its own function, but sometimes work as compensation for the CYP75A subfamily ( Xiao et al., 2021 ). In this study, all orchid CYP75 s were found to be located on the endoplasmic reticulum, as previous research has shown that CYP450 is a membrane protein primarily found on the ER membrane in eukaryotes ( Brignac-Huber et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on in the Swiss-Prot database, their functional domain was confirmed in silico as being compatible with the P450 superfamily. The CYP75A ( F3'5'H ) and CYP75B ( F3'H ) subfamilies can catalyze the conversion of apigenin to luteolin (KEGG: map0094) and perform hydroxylation of the B ring of flavonoids, important for the biosynthesis of blue and red anthocyanins (Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…where T、P are the temperature and pressure of the gas-liquid interface grid cell,  is a dimensionless coefficient related to the diameter [32][33][34]. Based on the classical Lee model, a gas-liquid phase change mass transfer model that considers bubble parameter factors can be derived.…”
Section: The Basic Physical Modelmentioning
confidence: 99%